2014
DOI: 10.1039/c4ra01651c
|View full text |Cite
|
Sign up to set email alerts
|

A catalyst-free, facile and efficient approach to cyclic esters: synthesis of 4H-benzo[d][1,3]dioxin-4-ones

Abstract: A metal and additive free base-mediated method for the formation of 4H-benzo[d][1,3]dioxin-4-one and its derivatives, from salicylic acids and dichloromethane, was developed using dichloromethane (DCM) and 1,1-dichloroethane (1,1-DCE) as the C1 source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…5,3]dioxin-4-ones, besides being used as useful intermediates in organic synthesis, 9 are present in insecticides 10 and compounds with anti-inflammatory, 11 antiulcer, 12 and antimicrobial 13 activities. They have previously been prepared by condensation of salicylic acid derivatives with aldehydes and ketones, 14 substitution of salicylic acid derivatives onto dichloromethane 15 and by iodoaromatization of enyne-dioxinones. 16 With the aim of optimizing and understanding this transformation we undertook a series of experiments (Tables 1 and 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,3]dioxin-4-ones, besides being used as useful intermediates in organic synthesis, 9 are present in insecticides 10 and compounds with anti-inflammatory, 11 antiulcer, 12 and antimicrobial 13 activities. They have previously been prepared by condensation of salicylic acid derivatives with aldehydes and ketones, 14 substitution of salicylic acid derivatives onto dichloromethane 15 and by iodoaromatization of enyne-dioxinones. 16 With the aim of optimizing and understanding this transformation we undertook a series of experiments (Tables 1 and 2).…”
mentioning
confidence: 99%
“…In less polar solvents (entries 6-9), the reaction did not proceed or proceeded with lower yields (40% in DMF, entry 6). Other Ag(I) salts, including Ag 2 CO 3 that is successfully used in the Fétizon's oxidation, 17 gave lower yields (entries [12][13][14][15]. Remarkably, it could be observed that the basicity of the counteranion the yield of 1b.…”
mentioning
confidence: 99%
“…The first approach was more efficient and had better yields. Cyclization in both routes was achieved using potassium phosphate tribasic, DCM, and DMF, under reflux with heating to 100 °C for 10 h. The reaction mixture was rechallenged with DCM every 3 h. The reaction was monitored by thin-layer chromatography (TLC) plates (mobile phase hexane in ethyl acetate 1:1), and upon completion, the mixture was extracted in DCM/water, according to the procedure reported in ref 19, and purified by flash chromatography using gradient elution from 0 to 100% ethyl acetate in hexane.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“… 7 For example, conversion of salicylic acid to benzo[ d ][1,3]dioxin-4-ones using dichloromethane as the methylene donor was reported by Xiuling Cui under catalyst-free condition using potassium phosphate. 8 Later, Liu et al developed a Cu(OAc) 2 catalyzed approach based on ortho -halobenzoic acid, KOH, and NaHCO 3 . 9 Morpholine catalyzed conversion of salicylic acid to the benzodioxinone scaffold was reported by Qiu and co-workers treating with ynones.…”
mentioning
confidence: 99%